Farmers suicide in India : dynamics and strategies of prevention - National Workshop on "Farmers suicides: dynamics and strategies of prevention"( National Institute of Rural Development, Hyderabad 2005); Gyanmudra; National Institute of Rural Development (India) (New Delhi : Deep & Deep Pub., 2007)
Contributed articles presented at the National Workshop held at the National Institute of Rural Development, Hyderabad
Includes bibliographical references and index
Keywords: Farmers -- Suicidial behaviour -- India -- Congressess; Suicide -- India -- Prevention -- Congressess; Suicide victims -- Rehabiliation -- India -- Congressess